Добро пожаловать в сказку! - Благов Владимир (Новые сказочные повести, 2009)
Экземпляры: ФО - 1; 9; 10; 12; 13; 15; 17; 18; 19; 22; (20110303) / Инвентарный номер: 46570 / Цена: 69.10 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 68 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6